A Workshop For Lecturer To Improve Their Competence - Muhammad Yusuf; Aep Saepudin; M Dana Prihadi; Kurhayadi Kurhayadi; Deden Hadi Kushendar; Riza Bahtiar Sulistyan (Universitas 17 Agustus 1945 Semarang, 2023)
This service aims to improve lecturer skill and comprehension of the application of instructional approaches in shaping the character of students at the Bandung College of Administrative Sciences in Cibeunying Kidul District, Bandung City. This dedication is motivated by the need for lecturers who are motivated to improve competency and who have the ability to use instructional tactics to shape students' character. The degree of the students' bad character and the lecturers' poor teaching techniques is the dull everyday instructional routine. This service took place on Thursday, June 3, 2023. Field surveys (locations), conversations, information collection, and lecturer observations were initially carried out in order to deliver this service. After that, teachers received training and help with regard to enhancing their competency as lecturers and putting character-development teaching methodologies into practise. The output objectives for this volunteer initiative include scientific publications, online content, YouTube activities, and photo documentation of PKM activities. It is common to use workshops, seminars, and question-and-answersessions.